2013
DOI: 10.1227/neu.0000000000000016
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Aneurysms Occur More Frequently at Bifurcation Sites That Typically Experience Higher Hemodynamic Stresses

Abstract: IAs occur more frequently at cerebral bifurcations that typically experience higher hemodynamic shear stress and stronger flow acceleration, conditions previously shown to promote aneurysm initiation in animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 38 publications
2
55
0
2
Order By: Relevance
“…4,5,13,14 Alfano et al 4 showed a significant association between a vessel bifurcation where aneurysms are frequent (ie, the ACoA complex, middle cerebral artery bifurcations, and ICA/posterior communicating artery junction) and high WSS. Studies on glass models revealed that the magnitude of hemodynamic stress increases proportionally to the bifurcation angle and asymmetry of the branch diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,13,14 Alfano et al 4 showed a significant association between a vessel bifurcation where aneurysms are frequent (ie, the ACoA complex, middle cerebral artery bifurcations, and ICA/posterior communicating artery junction) and high WSS. Studies on glass models revealed that the magnitude of hemodynamic stress increases proportionally to the bifurcation angle and asymmetry of the branch diameter.…”
Section: Discussionmentioning
confidence: 99%
“…However, we still do not know why intracranial aneurysms develop preferentially in certain arterial bifurcations, namely in the internal carotid artery (ICA)/posterior communicating artery junction, anterior communicating artery (ACoA) complex, and middle cerebral artery bifurcation. 4 This issue was partially addressed in glass model studies, showing that the magnitude and distribution of hemodynamic stress on the vessel bifurcation depend not only on blood flow but also on the bifurcation angle and flow pulsatility. 5,6 Also, our previous study showed that occurrence of cerebral aneurysms in the arteries constituting pathways of collateral circulation in patients with the occlusion of brachiocephalic vessels is not always related to the increase in blood velocity.…”
mentioning
confidence: 99%
“…22,24 Through detailed hemodynamics-histology mapping, we found that IA initiation at the BT (defined by regions of IEL loss) was associated with high WSS combined with positive WSS gradient above a threshold. 24,33 This hemodynamic condition, often associated with bifurcation apices, 34 has been recognized to independently cause de novo IA formation. 21,22,24,35 Kono et al 36 further provided clinical evidence that de novo BT aneurysms could be triggered by unphysiologically high local WSS and WSS gradient generated by proximal stenoses.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies conducted by Hashimoto et al 10 and Hazama et al 11 clearly showed that hemodynamic stress leads to degenerative changes of internal elastic lamina and muscularis media of arterial wall immediately adjacent to the apex of bifurcation. However, it is still not clear why aneurysms occur in some preferential site, like ACom complex, PCom complex and MCA bifarcation 12 . This issue was partially addressed in glass model studies, showing that the magnitude and distribution of hemodynamic stress on the vessel bifurcation depend not only on blood flow but also on the bifurcation angle and flow pulsatility [13][14] .…”
Section: Introductionmentioning
confidence: 99%